Roseau Bridge and Grandbay Street, Dominica - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2012)
Pedestrians, and a horse drawn cart cross the bridge into Grandbay Street. Gas lamps line the street in this circa 1909 scene. Handwritten on back: "Dominica (Roseau) [... A Italian ... Etruria". Postmark appears to indicate 1909. One penny Dominica postage stamp affixed to the bottom centre of the front of the postcard.
Landscape; black and white
Keywords: Bridges; Postcards; Trees; People; Carts and wagons; Utility poles